2009
DOI: 10.1159/000233290
|View full text |Cite
|
Sign up to set email alerts
|

Joint Involvement Associated with Inflammatory Bowel Disease

Abstract: Joint involvement associated with inflammatory bowel disease (IBD) belongs to the concept of spondyloarthritis (SpA) and includes two types of arthritis: a peripheral arthritis characterized by the presence of pauciarticular asymmetrical arthritis affecting preferentially joints of lower extremities and an axial arthropathy including inflammatory back pain, sacroiliitis and ankylosing spondylitis (AS). Treatment of arthritis includes a short-term use of NSAIDs associated with optimized treatment of gut inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…Treatment of, for instance, arthritis often includes a short-term use of non-steroidal anti-inflammatory drugs (NSAID) [49]. Previous results from the present research program showed that IBS cases of both sexes consumed significantly more analgesics than their controls did [50]. Registered diagnoses of thyroid disease, asthma, allergy, infections in the urinary tract as well as cardiovascular problems were more frequent among the IBS cases.…”
Section: Discussionmentioning
confidence: 84%
“…Treatment of, for instance, arthritis often includes a short-term use of non-steroidal anti-inflammatory drugs (NSAID) [49]. Previous results from the present research program showed that IBS cases of both sexes consumed significantly more analgesics than their controls did [50]. Registered diagnoses of thyroid disease, asthma, allergy, infections in the urinary tract as well as cardiovascular problems were more frequent among the IBS cases.…”
Section: Discussionmentioning
confidence: 84%
“…Joint inflammation often accompanies IBD in humans, and therefore a link between the two diseases has been suggested [42,43]. Though some mice seemed to have diarrhea chronically, most only showed signs transiently.…”
Section: Resultsmentioning
confidence: 99%
“…Although several case studies have been published about RA patients who developed IBD [73,74], IBD is not considered a typical extraarticular manifestation of RA [2,3]. In contrast, joint inflammation occurs in 20% of patients diagnosed with IBD, though it is classified as peripheral or axial spondyloarthritis [42,43] and is typically seronegative for RF and anticyclic citrullinated peptide antibodies [75,76]. …”
Section: Discussionmentioning
confidence: 99%
“…Transient spondyloarthritis occurs in 10-20% of patients with inflammatory bowel disease (IBD), usually during a flare of intestinal inflammation. 1 Current theories on the pathogenesis of IBD posit that inflammation results from an inappropriate immune response to gut bacteria in genetically predisposed individuals. Advances in metagenomic analysis of the gut microbiota have revealed that changes in the composition of the gut microbiota are commonly associated with IBD, although it remains unclear whether these changes are the cause or the result of intestinal inflammation.…”
Section: Out Of Joint: New Insights Into the Role Of Commensal Gut Bamentioning
confidence: 99%